ПОЗИЦІЯ АНГЛІЇ У СХІДНОМУ ПИТАННІ 1875-1878 рр. ЯК СКЛАДОВА ЧАСТИНА ПОЛІТИКИ “БЛИСКУЧОЇ ІЗОЛЯЦІЇ” (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of the position of Great Britain during the Eastern crisis of 1875- 1878 years, whether it had features of so called policy of “splendid isolation” which was held by this country in the 2nd part of the XIXth century.